Horatio Hornblower [videorecording (DVD)] : the adventure continues - Grieve, Andrew; Gruffudd, Ioan; Lindsay, Robert, 1949-; Warner, David, 1941- (A & E : Distributed by New Video, 2001)
Following his rapid rise through the ranks of the King's Navy, Hornblower is assigned to the HMS Renown which is sailing to the West Indies to subdue a pirate fleet. Her brutal captain is rapidly going insane forcing Hornblower to take action that threatens not only his naval career but his life as well.